UMP students return home as scheduled for semester break - Mimi Rabita, Abdul Wahit (2021)
PEKAN, 11 July 2021 - The long-awaited time is now approaching when students have the opportunity to return to their hometowns after completing the final examination of the 2020/2021 academic session recently.